Whole genome identification of CBF gene families and expression analysis in Vitis vinifera L. - Xiang Fang; Yiling Lin; Chun Chen; Tariq Pervaiz; Xicheng Wang; Hefei Luo; Jinggui Fang; Lingfei Shangguan (Czech Journal of Genetics and Plant Breeding, 2023)
The CBF (C-repeat binding factors) genes play important roles in response to abiotic stress and environmental changes. In the present study, a total of 18 CBF genes were identified from a grapevine. Their domains, phylogenetics, and collinearity were analysed. The results revealed, that 18 VviCBF genes were distributed on 10 chromosomes unevenly in the grape genome. Promoter data analysis showed that the CBF gene has many cis-acting elements related to plant growth and development, light response, hormone, and abiotic stress response. We found that six VviCBF genes including, VviCBF5, VviCBF13, VviCBF14, VviCBF15, VviCBF16, and VviCBF18 differentially expressed during fruit developmental stages. Furthermore, four VviCBF genes including, VviCBF1, VviCBF3, VviCBF6, and VviCBF11 were expressed at the early stage of bud dormancy, whereas, nine VviCBF genes were expressed at the bud dormancy-breaking stage. Additionally, various VviCBFs genes respond to different abiotic and biotic stress. These findings will lay a foundation for further study of the CBF genes in bud dormancy, downy mildew, and abiotic and biotic stresses.